Optimalisasi Peran Kader Posyandu dalam Program Gerakan Cegah Stunting di Puskesmas - Wahyuni, Sari; Eprila, Eprila; Nursanti, Rina; Maharani, Tarisa; Putri, Salsabillah; Wulandari, Tri (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Stunting is a public health problem that requires continuous intervention, especially during the first 1,000 days of life. It remains a serious issue in Indonesia's health development, primarily due to the limited capacity of Posyandu cadres in early detection and preventive education. This community service activity aimed to improve the capacity of Posyandu cadres in detecting and preventing stunting. The program was conducted at Puskesmas Pembina Palembang in October 2024, involving 20 active Posyandu cadres. The method included preparation, pre-test, educational sessions, discussions, question and answer, and final evaluation. Initial assessments revealed that most cadres lacked sufficient knowledge and skills regarding stunting risk signs and child growth monitoring. Following the educational intervention and training, there was a significant increase in the cadres’ knowledge and communication skills in delivering nutrition education and performing early stunting detection. This activity made an important contribution to supporting the national program to accelerate stunting reduction and is recommended to be replicated in other Puskesmas service areas.